Enhance production of MnP by Phanerochaete Chrysosporium and evaluation of glyphosate degradation - Minh Quang, Nguyen; Hoai Diem Phuong, Le; Bao Uyen, Luong (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2SDO - 10.25073/2588-1140/vnunst.4566, 2017)
Ligninolytic enzymes include Manganese peroxidase enzymes, Lignin peroxidase (LiP), Laccase (Lac) have ability to degrade lignin and difficult decomposition complexes. Many studies proved that ligninolytic enzymes have ability to degrade glyphosate. In which, Manganese peroxidase (MnP) produced by Phanerochaete Chrysosporium , a white rot fungus, have ability to degrade glyphosate. Therefore, one of the ways to increase glyphosate degradation efficiency is to increase the MnP activity of Phanerochaete chrysosporium . The objective of this study was to increase the efficiency of glyphosate degradation by investigating the effect factors (such as glucose, ammonium tartrate concentration and culture time) to increase the MnP biosynthesis from Chrysosporium Phanerochaete . The fungus produced highter level of MnP (up to 49.75 UI/L) when the glucose concentration was 0.2%w/v, the ammonium tartrate concentration was 5 g/l, and the culture time was 9 days. MnP of Phanerochaete chrysosporium was able to degrade 40% glyphosate after 24h incubated.